2018
DOI: 10.1111/ajsp.12328
|View full text |Cite
|
Sign up to set email alerts
|

Can we forgive a militant outgroup member? The role of perspective‐taking

Abstract: Whereas previous research has commonly studied the effects of perspective‐taking for harmless targets, we examined whether the effect of perspective‐taking might extend to a violent outgroup target. That is, our target not only held members of the adversary group responsible for his plight but also issued a severe threat to them (suicide bombing). We report findings from two studies that were conducted within the intergroup relations between Israelis and Palestinians, defined by a prolonged and violent conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Guilt and shame might promote group apologies and material compensations, but these emotions do not work beyond empathy and anger, and they do not form a solid basis for general opposition to inequality (as signposted in the correlation table). Corroborating the key role of empathy, Noor and Halabi (2018) revealed that experimentally inducing empathy towards outgroup members (even violent ones, such as terrorists) among Israelis can foster forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Guilt and shame might promote group apologies and material compensations, but these emotions do not work beyond empathy and anger, and they do not form a solid basis for general opposition to inequality (as signposted in the correlation table). Corroborating the key role of empathy, Noor and Halabi (2018) revealed that experimentally inducing empathy towards outgroup members (even violent ones, such as terrorists) among Israelis can foster forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite normatively expected to have abandoned radical ideologies in order to be involved in CVE initiatives, Tapley and Clubb (2019) encourage returnees to be actively engaged in CVE while "provided support regardless of whether they have abandoned their ideology" (Tapley and Clubb, 2019, p. 14). Noor and Halabi (2018) note that the integrated threat theory (ITT) (Noor andHalabi, 2018, referencing Stephan andStephan, 2000) predicts that "[t]he more we perceive someone as threatening, the more negative will be our attitudes toward them" (Noor and Halabi, 2018, p. 247), while combining this with research on how perspective taking improves intergroup attitudes (Noor and Halabi, 2018, p. 247). Noor and Halabi (2018) found that perspective-taking improves interpersonal liking, which in turn correlates with the motivation to forgive an individual, even in violent conflicts and contexts where one party is, or is perceived to, issue a threat to the other party (Noor and Halabi, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process allows returnees to reflect on the importance of engaging with other returnees, "to make them feel human" (R5), and community members through "day to day activities" (R3), while community members account for the importance of engaging with other community members, victims of terrorism, as well as returnees. Community members illustrate, despite VE having caused them individual and significant suffering, a willingness and ability for perspective taking in relation to those who may or may not be perceived as representatives of a societal threat, which is argued to relate to the motivational aspects for forgiveness (Noor and Halabi, 2018). None of the participants had envisioned the other groups to see their body maps, but the findings reveal that many of the perceptions upheld could be mitigated were the respective groups exposed to the body maps and testimonials of the others.…”
Section: Suggestions For Practitioners and Ideas For Future Researchmentioning
confidence: 99%
“…The benefits of perspective taking for intergroup relations have been well documented. Taking the perspective of an outgroup lowers stereotyping and prejudice (Galinsky & Moskowitz, 2000), limits the denial of discrimination (Todd et al., 2012), promotes intergroup helping (Bilewicz, 2009) and conflict resolution (Batson et al., 2002), and increases positive evaluation of outgroups (Batson et al., 2002), intergroup forgiveness (Noor et al., 2008; Noor & Halabi, 2018), and willingness to engage in intergroup contact (Wang et al., 2014). Because of these benefits, perspective‐taking tasks are often embedded in interventions to address intergroup conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…Listening to the story by taking the protagonist's perspective, as compared with an objective perspective, reduced prejudice toward the Roma. Noor and Halabi (2018) found that a perspective‐taking manipulation increased outgroup liking and forgiveness among Israelis in the context of Israeli‐Palestinian conflict. Finally, in online intergroup dialogues among Mexicans and Whites in the U.S., and Israelis and Palestinians in Israel, a perspective‐taking task that involved participants summarizing the statement of their discussion partner improved intergroup outcomes among dominant group members (i.e., for Whites and Israelis; Bruneau & Saxe, 2012).…”
Section: Introductionmentioning
confidence: 99%